Frequency of Serous Otitis Media in Children without Otolaryngological Symptoms - Kocyigit,Murat (2017)
Abstract Introduction Otitis media with effusion is the fluid in the middle ear with no signs or symptoms of acute ear infection. Objective This study aims to research the frequency of serous otitis media in patients referred to the pediatric clinic between 3-16 years of age without any active ear, nose, and throat complaints. Methods This study included 589 children patients (280 boys, 309 girls; mean age: 9.42; range 3-16) who were administered to the pediatric clinic without otolaryngologic complaints. Patients underwent examination with flexible nasopharyngoscopy for adenoid hypertrophy. An otorhinolaryngologist examined all children on both ears using an otoscope and tested with tympanometry. We used tympanometry results to diagnose SOM. Results The study included 589 patients that underwent fiber optic examination of the nasopharynx with an endoscope. Adenoid vegetation was present in 58 patients (9.8%) and was not detected in 531 patients (90.2%). We found serous otitis media in 94 (15.9%) patients. We obtained Type A tympanogram in 47 (81%) of 58 patients with adenoid vegetation, 6 (10.3%) Type B, and 5 (8.6%) Type C.When comparing 58 patients with adenoid vegetation with 538 patients without adenoid vegetation for serous otitis media, the frequency was not statistically significant (p > 0.05). Conclusion We believe that in children without any ear, nose, and throat complaints, it is possible to detect serous otitis media with adenoid vegetation. Thus, pediatric patients should undergo screening at regular intervals.